Globalization, Security and Governance Challenges in Nigeria - WILSON SIMON OKWOLI; LAMI LENTON ANUGA; JOSEPH ABOGENYE ANUGA (International Studies Journal)
The study focused on the nature of the challenges and opportunities the process of globalization imposes on the development of the security sector of the Nigerian state. Security challenges such as insurgency and political agitations relying on terrorism were studied in the context of a globalized world. The Instrumental Theory of Insecurity was adopted as the theoretical framework guiding the study. Secondary sources of data were used relying on content analyses and the literary critical method for analyses of the data. The study found that residual authoritarian constructs still pervade Nigerian society and as such the peaceful processing of conflicts have not been adequately prioritized as policy across the country. It also found that the inability of the Nigerian state to deliver on material development aspirations of citizens exposes the country to global terrorist actors who highjack the difficulties of governance to pursue their own ends. This study contributes to knowledge in a number of ways, including by attempting to pinpoint the prominent role that violent non-state actors in play on the global stage in subverting the governments by reenacting the narratives surrounding violent extremism with ethnic and religious overtones in an effort d to benefit economically and politically from the outcomes. That is a defining attribute of terrorist organizations that are active in Nigeria with their international links. The study also shows that the international system has been successful in establishing substitute routes for supply chains and communication that circumvent the legal exchange route for the transfer of illegal goods and money between nations, compromising the ability of those nations to survive. The study therefore recommended that Nigeria need to be at the forefront of promoting the establishment of a strong economic bloc among African nations with the goal of curbing the explosive trend of globalization toward the proliferation of weapons and other types of transnational crimes. Also, Nigerian state should prioritize good and inclusive government to reorient citizen loyalties, mechanisms oriented towards the peaceful processing of conflicts and seriously engage in delivering on economic development for its citizens through adopting modern economic practices and enforcing global best practice protocols for public institutions within the state.